The Effectiveness of the Death Penalty as an Instrument of Legal Firmness Against Drug Dealers - Putratama, Muhammad Rafly; Laksana, Andri Winjaya (UNISSULA Semarang, 2025)
Illegal drug trafficking in Indonesia has reached a very alarming level and is a serious threat to national resilience, so that the state has taken a firm legal policy through the application of the death penalty to drug dealers as regulated in Law Number 35 of 2009 concerning Narcotics. The death penalty is believed to be a form of ultimum remedium as well as an effective deterrent instrument to overcome this extraordinary crime. However, its effectiveness is still being debated, especially due to the lack of empirical evidence that the death penalty can significantly reduce the number of drug crimes. In writing this thesis, the aim is to study and analyze the effectiveness of the application of the death penalty to drug dealers in the criminal law system in Indonesia and to study and analyze the obstacles and solutions in the application of the death penalty to perpetrators of drug crimes in Indonesia. The method used is an empirical juridical legal approach, which combines normative analysis of laws and regulations with the reality of their application in the field. Data were collected through document studies, interviews with law enforcement officers, and observations of a number of court decisions that imposed the death penalty on perpetrators of narcotics crimes. The author uses the theory of Effectiveness of Law Enforcement and the theory of legal certainty to analyze the effectiveness of the application of the death penalty to drug dealers in the criminal law system in Indonesia, obstacles and solutions in the application of the death penalty to perpetrators of drug crimes in Indonesia. Factors such as weak oversight systems, potential abuse of authority, and lack of consistency in law enforcement are major obstacles. In addition, the death penalty also raises controversy in the context of human rights, especially the right to life. Therefore, an evaluation of the death penalty policy and strengthening of a transparent and accountable justice system are needed as part of a more effective drug control strategy. The government needs to reform the Narcotics Law to clarify the criteria for applying the death penalty, so that it includes not only big drug lords but also dealers involved in drug distribution networks at various levels, in order to provide legal clarity and ensure justice for all perpetrators. In addition, the effectiveness of its implementation must be supported by ongoing training and education for law enforcement officers to improve integrity and prevent errors in the sentencing process.